2016
DOI: 10.5194/amt-9-133-2016
|View full text |Cite
|
Sign up to set email alerts
|

UTLS water vapour from SCIAMACHY limb measurementsV3.01 (2002–2012)

Abstract: Abstract. The SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) aboard the Envisat satellite provided measurements from August 2002 until April 2012. SCIAMACHY measured the scattered or direct sunlight using different observation geometries. The limb viewing geometry allows the retrieval of water vapour at about 10-25 km height from the near-infrared spectral range (1353-1410 nm). These data cover the upper troposphere and lower stratosphere (UTLS), a region in the atmosphere wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…The 2σ error or uncertainty ranges also plotted indicate that the water vapour linear changes are not statistically significant at altitudes above 37 km and between 20 and 30 km where the change switches sign. A positive linear change in lower stratospheric water vapour during the time interval considered in this study has been observed by and Weigel et al (2016) mainly in the tropics. As already discussed in Noël et al (2016) methane linear changes are also not significant except for the lowest altitudes, where they are in general agreement with tropospheric trends.…”
Section: Linear Changessupporting
confidence: 62%
“…The 2σ error or uncertainty ranges also plotted indicate that the water vapour linear changes are not statistically significant at altitudes above 37 km and between 20 and 30 km where the change switches sign. A positive linear change in lower stratospheric water vapour during the time interval considered in this study has been observed by and Weigel et al (2016) mainly in the tropics. As already discussed in Noël et al (2016) methane linear changes are also not significant except for the lowest altitudes, where they are in general agreement with tropospheric trends.…”
Section: Linear Changessupporting
confidence: 62%
“…A comprehensive overview of commonly applied airborne instrumentation is given by Wendisch and Brenguier (2013). During the ML-CIRRUS and ACRIDICON-CHUVA campaigns, a set of remote sensing and in situ instruments was operated aboard HALO Voigt et al, 2017).…”
Section: Airborne Instrumentationmentioning
confidence: 99%
“…Molleker et al (2014) showed that the CCP exhibits a nominal limit for cloud particle diameters from 3 up to 50 µm. The CIPgs records twodimensional shadow images of cloud particles in a size range from 15 up to 960 µm with an optical resolution of 15 µm (Klingebiel et al, 2015;Weigel et al, 2016). Special algorithms are used to process and analyze the captured images in order to estimate particle number concentrations and particle size distributions, and to differentiate particle shapes (Korolev, 2007).…”
mentioning
confidence: 99%
“…The 2σ uncertainty ranges also plotted indicate that the water vapour trends are not significant in a statistical sense at altitudes above 37 km and between 20 and 30 km where the trend switches sign. A positive trend in lower stratospheric water vapour during the time interval considered in this study has been observed by Urban et al (2014) and Weigel et al (2016) mainly in the tropics. As already discussed in Noël et al (2016) methane trends are also not significant except for the lowest altitudes, where they are in general agreement with tropospheric trends.…”
Section: Potential Watermentioning
confidence: 83%